A bridge over troubled water: A contextual analysis of social vulnerability to climate change in a riverine landscape in south-east Norway. Issue 4 (7th August 2016) - Gundersen, Vegard; Kaltenborn, Bjørn Petter; Williams, Daniel R.
ABSTRACT: Local communities in the Gudbrandsdalen region in Norway are increasingly exposed to climate-induced hazards such as floods and landslides. A core question is how community members respond to climate change and what factors contribute to more resilient communities. The authors used a contextual approach to analyze data from semi-structured interviews along five dimensions. In Gaustad Muncipality they found that individuals' motivation to adapt to climate change depended largely on subjective values such as identity, place attachment, cultural values, and social networks among individuals, which means it is crucial that strategic plans for adaptation to climate change at different policy levels are experienced as relevant by community members. While the studied community has experienced heavy floods in river systems and streams, little evidence of adaptation was observed. Instead, they appeared to adopt coping strategies. Landowners may have limited incentives to adapt to climate change due to contraproductive policy measures such as economic compensation for direct losses without requiring improved practices. Effective adaptation to climate change on the local level is likely to require making compensation mechanisms contingent upon landowners showing willingness to change from coping to adaptive practices, as well as a contextualized approach integrating local and scientific forms of knowledge.